A prosopographic study of the New Kingdom Tomb Owners of Dra Abu El-Naga - Jiménez-Higueras, Ángeles (Archaeopress Egyptology, 2022)
Containing the dating, kinship data and titles for each tomb owner of 54 tombs located in the southern area of the Theban cemetery of Dra Abu el-Naga during the New Kingdom, this book will prove of great assistance as a handbook or catalogue for research on New Kingdom Dra Abu el-Naga or the study of prosopography and kinship relationships.